УДОСКОНАЛЕННЯ КОМП'ЮТЕРНОЇ ІМІТАЦІЙНОЇ МОДЕЛІ ЧАСТОТНО-РЕГУЛОВАНОГО АСИНХРОННОГО ДВИГУНА В ПАКЕТІ ПРОГРАМ MATLAB - Волков, В.О. (Інститут електродинаміки НАН України, Київ, 2026)
The article is devoted to improving the well-known computer simulation model of a three-phase squirrel-cage induction motor with frequency control (which is present in the MATLAB software package). This improvement the simulation model consists in expanding its functionality (in particular, carrying out a refined calculation of the instantaneous values of all types of basic power losses, basic active power consumption, and energy indicators of the motor) and increasing the precision of finding the instantaneous values of the basic harmonic components of the motor's phase stator currents in steady-state and start-braking modes. This task was solved by supplementing the abovementioned well-known model from the MATLAB software package with refined analytical dependencies for calculating the main energy parameters of a frequency-regulated induction motor and as because of obtaining new refined analytical calculation dependencies for determining the instantaneous value of the modulus of the generalized stator current vector of this motor. To confirm the capacity for work of the improved computer simulation model, the following parameters were calculated using it (for a squirrel-cage induction motor loaded with a centrifugal fan) in steady and start-braking modes of the motor: its basic power losses and basic active power consumption, efficiency and power coefficients. The practical value of the improved computer simulation model consists in increasing the precision of calculating the electromagnetic and energy processes of a frequency-regulated induction motor in steady and start- braking modes under scalar control. References 18, figures 4, tables 2.